In vitro study of antimicrobial activity of fermented coconut water extrected with different solvents against pseudomonas fuscovaginae, causal agent of sheath brown rot of rice / Nurul Basyeroh Hasan - Hasan, Nurul Basyeroh (Faculty of Plantation and Agrotechnology, 2018)
Sheath Brown Rot (SBR) caused by Pseudomonas fuscovaginae is a devastating bacteria rice disease, currently getting an attention from researchers and government from various countries. Such a control management is on how to control the disease from spread and become more serious. Hence, the aim for study, is to screening antimicrobial activity of fermented coconut water extracted with different solvents against pathogen of SBR and to determine Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of fermented matured coconut water extracted with different solvents. The inhibition zone was determined using agar well difussion method and the result showed that the aqoues and methanol extraction give a reaction to the pathogen. The highest inhibition zone was on methanol extraction with the mean of inhibition zone diameter where recorded is 2.02 cm. Meanwhile, for determination of MIC and MBC for methanol extract, it was discovered that 20% concentraction of the exctract was enough to inhibit the growth the pathogen and 30% concentraction could kill the pathogen. This study suggested that methanol extract could be used as formulation for fermented mature coconut water in controlling SBR.